Amelioration of methane production efficiency of paper industry waste sludge through hydrolytic enzymes assisted with poly3hydroxybutyrate. (1st January 2021) - Sethupathy, A.; Sivashanmugam, P.
Abstract: In this study, the methane production potential of paper industry waste sludge (PPWS) was investigated using consortium of hydrolytic enzymes (CHE) mediated poly3hydroxybutyrate ( P3HB) method. Initially, P3HB was extracted from municipal aerated waste sludge (MARWS) by optimizing extraction time and dimethyl carbonate dosage. Maximum of P3HB (910 mg/g) was extracted at 60 min of extraction time and 4 mL of dimethyl carbonate dosage. Then, the influence of extracted P3HB dosage (5–120 mg) on methane production from PPWS was examined. 75 mg of P3HB dosage was exhibited higher methane production (153 mL/g VS) when compared to other P3HB dosage. Further, CHE mediated pretreatment was performed by varying CHE dosage and temperature. At optimized CHE dosage (2.5 mL) and temperature (45 °C), maximum of chemical oxygen demand (COD) liquefaction, suspended solids reduction (SSR) and lignin removal were found respectively to be 23.7%, 18% and 61% which was higher than control (COD liquefaction (0.9%), SSR (0.5%) and lignin removal (0.7%)). Also, biomethane potential assay was carried out in which CHE mediated P3HB method attained higher methane production (280 mL/g VS) when compared to CHE method (217 mL/g VS) and control (47 mL/g VS). Highlights: Biopolyester was extracted by varying extraction time and dimethyl carbonate dose. The extracted biopolyester was identified as P3HB. P3HB dose had a significant impact on methane production from PPWS. Maximum of COD liquefaction and SSR were noticed in CHE pretreatment study. Higher methane production was attained by CHE mediated P3HB method.